2010
DOI: 10.1177/0020764009341211
|View full text |Cite
|
Sign up to set email alerts
|

Stresses Experienced By Psychiatrists and Their Role in Burnout: a National Follow-Up Study

Abstract: Most factors associated with burnout are preventable and can be managed jointly between psychiatrists and administrators. Service providers need to address burnout seriously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 21 publications
0
37
0
6
Order By: Relevance
“…Low social support is a major predictor of occupational stress in doctors and nurses (Wu, Ge, Sun, Wang, & Wang, 2011;Wu, Zhao, Wang, & Wang, 2010); particularly in psychiatrists, high levels of social support are most strongly associated with low levels of poor mental health (Umene-Nakano et al, 2013). Receiving social support for work-related problems reduces work-related exhaustion and increases mental energy in psychiatrists (Shailesh, Simon, Gaelle, Jesse, & Etuini, 2011). In addition to families, friends and relatives, support from those in their working environment, such as colleagues, managers and patients, might help to lessen occupational stress in psychiatrists.…”
Section: Implications For Program Improvement In Chinamentioning
confidence: 99%
“…Low social support is a major predictor of occupational stress in doctors and nurses (Wu, Ge, Sun, Wang, & Wang, 2011;Wu, Zhao, Wang, & Wang, 2010); particularly in psychiatrists, high levels of social support are most strongly associated with low levels of poor mental health (Umene-Nakano et al, 2013). Receiving social support for work-related problems reduces work-related exhaustion and increases mental energy in psychiatrists (Shailesh, Simon, Gaelle, Jesse, & Etuini, 2011). In addition to families, friends and relatives, support from those in their working environment, such as colleagues, managers and patients, might help to lessen occupational stress in psychiatrists.…”
Section: Implications For Program Improvement In Chinamentioning
confidence: 99%
“…Psychiatrists often work with threatening patients in isolation, experience violence and patient suicide, need to make critical decisions within multidisciplinary teams with unclear role definitions, and have to predict the risk of loss of life or serious injury when discharging difficult patients 9 . A recent study also lists long working hours, an aggressive administrative environment, and low pay as major correlates of emotional exhaustion among psychiatrists 10 . An important consequence of the above conditions seem to be the recent crisis in the recruitment and retention of psychiatrists, both in the UK and abroad 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Kumar et al found that psychiatrists invariably gave higher scores to factors described as protective against burnout: job satisfaction and professional supervision. 19 Kara et al found that being employed as psychologist was linked to greater PA. 20 In many parts of the world, psychosocial specialists, including psychologists, psychiatrists, social workers, and counselors, address the psychological and emotional needs of cancer patients and their families. 21 Only 1 study has published the prevalence of burnout among psychosocial specialists working in oncology.…”
mentioning
confidence: 99%